2012
DOI: 10.1039/c2cp23479c
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the D+ + H2 and H+ + D2 reactions: a detailed comparison between theory and experiment

Abstract: ion-molecule reactions is compared with the results of quantum mechanical (QM), quasiclassical trajectory (QCT), and statistical quasiclassical trajectory (SQCT) calculations. The dynamical observables considered include specific rate coefficients as a function of the translational energy, E T , thermal rate coefficients in the 100-500 K temperature range. In addition, kinetic energy spectra (KES) of the D + ions reactively scattered in H + + D 2 collisions are also presented for translational energies between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 74 publications
1
40
0
Order By: Relevance
“…In that work, Honvault and Scribano concluded that their results for the j = 0 case were about between two and four times smaller than the statistical predictions of McCarroll; 51 for the reaction initiated with H 2 (v = 0, j = 1) however the TIQM rates were found larger than those statistical results. In turn, the value at T = 100 K reported by Jambrina et al 47 As in the case of the H + +H 2 reaction, 4, 56 the statistical predictions are found to reproduce correctly the qualitative behaviour of the TIQM results as a function of the temperature. In addition, the comparison with the TIQM values shows that the quantitative agreement is also remarkable.…”
Section: B Rate Constantsmentioning
confidence: 62%
See 3 more Smart Citations
“…In that work, Honvault and Scribano concluded that their results for the j = 0 case were about between two and four times smaller than the statistical predictions of McCarroll; 51 for the reaction initiated with H 2 (v = 0, j = 1) however the TIQM rates were found larger than those statistical results. In turn, the value at T = 100 K reported by Jambrina et al 47 As in the case of the H + +H 2 reaction, 4, 56 the statistical predictions are found to reproduce correctly the qualitative behaviour of the TIQM results as a function of the temperature. In addition, the comparison with the TIQM values shows that the quantitative agreement is also remarkable.…”
Section: B Rate Constantsmentioning
confidence: 62%
“…47, the D + +H 2 process has been experimentally studied at much more extent for higher values of T. Fehsenfeld et al 15 reported a value larger than 0.7 × 10 −9 cm 3 molec −1 s −1 at T = 80 K and almost independent value with respect to the temperature of about 1.0 × 10 −9 cm 3 molec −1 s −1 with error bars of +0.5/ − 0.25 × 10 −9 cm 3 molec −1 s −1 for the range 100 K < T < 287 K. Both experimental results remain below the output of both theoretical results obtained in the present study. The k SQM (T) results overestimate the measured rate constants, as observed beyond E c ∼ 0.04 eV in the comparison established by Jambrina et al 47 for rate constants as a function of the energy for the title reaction calculated by means of the SQCT approach and measurements from ion beam investigations.…”
Section: B Rate Constantsmentioning
confidence: 99%
See 2 more Smart Citations
“…45,46 This procedure has been applied recently to the study of the triatomic D + + H 2 and H + + D 2 reactions providing a very good agreement with experiments. 47 However, in the present five-atom case the ZPE is very high. This implies a very wide energy range of internal energy of the two products.…”
Section: Quasi-classical Trajectory Calculationsmentioning
confidence: 68%